If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -63 = -7y Solving -63 = -7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7y' to each side of the equation. -63 + 7y = -7y + 7y Combine like terms: -7y + 7y = 0 -63 + 7y = 0 Add '63' to each side of the equation. -63 + 63 + 7y = 0 + 63 Combine like terms: -63 + 63 = 0 0 + 7y = 0 + 63 7y = 0 + 63 Combine like terms: 0 + 63 = 63 7y = 63 Divide each side by '7'. y = 9 Simplifying y = 9
| 3y-7x=5 | | -4m+8(-6m-3)=4(-4m+3) | | -12n=7 | | 2(x-5)-3(2x-7)=12-5(3x+1) | | x^2-4x-428=0 | | 7(x-2)+2x=22 | | 2.7x+1.05=5.7x | | 3(b-4)=21 | | 9x-12=4x+23 | | 4(x)-(x+2)=12+2(x+4) | | 3(15x+25)=435 | | 4x-(x+2)=12+2(x+4) | | 8+12b-26+6b=0 | | f(-3)=x^2+1 | | 15x-10=225 | | (15+3x)-x=65 | | 3.9y+9.6=8.7y | | 4x-x+2=12+2(x+4) | | 2b+6=9b+11 | | 7(2x+4)=77 | | 12x-20=12x | | 4(-4-8x)+28x+4x=-273 | | 3(x^2+5x+6)=0 | | 4+b=1 | | -20=4(d-2) | | 1+j=2 | | -0.3+r=4 | | 4x-x+12=12+2(x+4) | | 19+j=107 | | 16=4(X-3) | | n-14=-20 | | 3p-9=90 |